Dukungan orang tua dan kepercayaan diri sebagai prediktor bersama motivasi prestasi pada atlet dansa olahraga Indonesia - Samosir, Agussalim; Malona Sitorus , Sefty; Sahputera Sagala, Ramlan; Muchlisin Natas Pasaribu, Ahmad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Dancesport, as a discipline that combines artistic performance and competitive sport, requires technical mastery and strong psychological readiness. Achievement motivation becomes a critical performance determinant, shaped by internal and external factors. This study analyzed the influence of parental support and self-confidence on the achievement motivation of North Sumatra dancesport athletes competing at PON XXI Aceh–North Sumatra 2024. A quantitative approach with an ex post facto survey design was applied. The sample consisted of 10 randomly selected athletes, ensuring that all eligible participants were included in the study. Data were collected using validated Likert-scale questionnaires, and instrument validity was confirmed through expert review, pilot testing, and Cronbach’s Alpha reliability (all > 0.70). Data analysis was conducted using simple and multiple regression with SPSS 26. The results showed that parental support significantly influenced achievement motivation (F = 7.842; p = 0.012), self-confidence also had a significant positive effect (F = 18.074; p = 0.002), and their combination significantly contributed to motivation (F = 6.215; p = 0.028), explaining 64.7% of the variance. These findings conclude that the synergy of external support and internal psychological capital shapes achievement motivation in dancesport. The practical implication is that athlete development programs must integrate parental involvement with structured confidence-building strategies. Theoretically, this study contributes to integrating social support theory and achievement motivation theory in the Indonesian sports context, emphasizing the role of both social and psychological dimensions in athlete development.